ETIKA AMAR MA’RUF NAHI MUNKAR MENURUT AL-GHAZALI DAN RELEVANSINYA DALAM PENDIDIKAN ISLAM - M. Alvin Hidayatulloh; Ali Mohtarom; Askhabul Kirom; Ahmad Ma'ruf (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the concept of the ethics of amar ma‘ruf nahi munkar according to Imam Al-Ghazali and to explain its relevance in Islamic education, particularly in the moral development of students and the role of educators. Method: This research employed a qualitative approach using a library research design. Primary data were obtained from the book Ihya’Ulum al-Din by Imam Al-Ghazali, particularly the discussion on hisbah or amar ma‘ruf nahi munkar, while secondary data were collected from relevant journals, books, and previous studies. Data analysis was conducted descriptively and analytically through data reduction, data presentation, and conclusion drawing. Results: The findings indicate that Imam Al-Ghazali viewed amar ma‘ruf nahi munkar as a fundamental pillar of religion that must be implemented based on specific ethical principles, namely knowledge, wara’ (piety), and husnul khuluq (noble character). Its implementation is carried out gradually (tadarruj), beginning with identifying wrongdoing, providing explanation, giving advice, and taking appropriate action according to authority while considering benefits (maslahah) and harms (mafsadah). In Islamic education, this concept is relevant through humanistic, pedagogical, and exemplary approaches by educators in fostering students’ character. Novelty: This study offers a reinterpretation of the ethics of amar ma‘ruf nahi munkar from Al-Ghazali’s perspective as a moral development model adaptable to the challenges of contemporary Islamic education in the digital era.